EDUKASI PEMBUATAN BILIK DISINFEKTAN SEDERHANA MELALUI VIDEO BAGI MASYARAKAT DI TENGAH PANDEMIK COVID-19 - Yunardi, Riky Tri; A'yun, Qurrotul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The purpose of this community activity is to provide education to make simple disinfectant chamber for people who have a lot of potential, especially in preventing the spread of the covid-19 virus. This design consists of a chamber made of an aluminum frame covered with transparent PVC plastic. In order to be entered by an adult human, the size of the design has a height and length of 200 cm and a width of 100 cm. As a disinfectant liquid sprayer, it is equipped with a 2-3 micron nozzle spray and a water pump motor integrated with electronic devices and control systems. The liquid tank is designed to accommodate a mixture of water and disinfectant substances and it is connected to the water pump using a PVC pipe. In the implementation of this community service activity, a video was made about the education of the use and how to make a disinfectant chamber. The results of the prototype and video can be used to facilitate people who want to make disinfectant chambers independently.